Answer:
The correct equation is the first one
S(s) + O2(g) → SO2(g)
Step-by-step explanation:
Step 1: Data given
Sulfur = S
combustion reaction = adding O2
sulfur dioxide = SO2
Step 2: The unbalanced equation
S(s) + O2(g) → SO2(g)
This equation is already balanced.
2H2S + 3O2 → 2H2O + 2SO2
In this reaction sulfur dioxide is generated. But the reactants are Hydrogen sulfide (H2S) and oxygen gas (O2)
4FeS2 + 11O2 → 2Fe2O3 + 8SO2
In this reaction sulfur dioxide is generated. But the reactants are Ferrous disulfide (Fe2) and oxygen gas (O2)
2SO2 + O2 → 2SO3
In this reaction sulfur dioxide is the reactant. The combustion of sulfur dioxide will give sulfur trioxide.
The correct equation is the first one
S(s) + O2(g) → SO2(g)